Peak instantaneous PlayerLoad metrics highlight movement strategy deficits in professional male soccer players - Mitchell, A.; Greig, M. (Research in Sports Medicine, 2022)
To investigate the influence of task, limb dominance and previous injury on single leg hop task performance and loading response, 25 professional male soccer players completed anterior, medial and lateral hop tests with an accelerometer at mid-calf. Performance outcome was defined as hop distance with loading response defined as the magnitude of, and time to peak instantaneous planar PlayerLoad. The performance was sensitive to task and previous injury (P < 0.001) but not limb dominance, with no evidence of bilateral asymmetry (P = 0.668). Despite impaired performance, previously injured players did not exhibit lower peak instantaneous PlayerLoad after impact in any plane (P = 0.110). There was however a significantly (P = 0.001) longer time to peak medio-lateral loading after impact in previously injured players` affected limb. This observation was exacerbated when the injury was to the non-dominant limb (P = 0.041). Lower-limb accelerometry enhances understanding of movement strategy beyond task outcome, with practical implications in player screening and objective rehabilitation.